Metastatic hepatocellular carcinoma presenting as a lytic calvarial mass - Shirley Parraga; Melisa Pasli; Hayley Behm; Breann Zeches; Revanth Reddy (Clinical Case Reports)
Key Clinical Message Hepatocellular carcinoma (HCC) is one of the most common types of cancer. More focus is being placed on clinical presentations of distant metastasis from HCC. Head masses should be investigated even when no concerning symptoms are found in patients with prior history of alcohol abuse and liver comorbidities.